Measuring Some Mechanical Properties of Boxwood and Privet Plants by an Izod Impact Tester - Mohammad Reza Kamandar; Jafar Massah; Farhad Khoshnam (Biomechanism and Bioenergy Research, 2022)
The information of the impact cutting behavior of plants stalk, play an important role in the design and fabrication of plants cutting equipment. It is difficult to investigate a theoretical method to define cutting properties of plants stalks because the cutting process is complex. Thus, it is necessary to set up an experimental approach to determine cutting parameters for a single stalk. To measure the shear force, shear energy and shear strength of plant stalk, a special impact cutting tester was fabricated. The apparatus included four strain gages and a digital indicator to show the real-time cutting force and requirement cutting energy of plant stalk. To test the apparatus, a series of laboratory tests were conducted to measure the shear force, shear consumption energy and shear strength of stem internodes of two plants stalk like boxwood or box with a scientific name of Buxus (Buxus Sp) and privet with a scientific name of Ligustrum Ovalifolium (Oleaceae Sp) under impact cutting at four loading rates (1, 2, 3 and 4 m/s) and three internodes of stalk (fifth, tenth and fifteenth). At boxwood cutting analysis: the minimum and maximum values of shear consumption energy were obtained as 3.19 J at fifth internode and loading rate: 4 m/s and 19.6 J at fifteenth internode and loading rate: 1 m/s, respectively. The minimum and maximum values of shear strength were obtained as 0.06 MPa at fifth internode and loading rate: 4 m/s and 1.55 MPa at fifteenth internode and loading rate: 1 m/s, respectively. At privet cutting analysis: the minimum and maximum values of shear consumption energy were obtained as 3.95 J at fifth internode and loading rate: 4 m/s and 28.56 J at fifteenth internode and loading rate: 1 m/s, respectively. The minimum and maximum values of shear strength were obtained as 0.2 MPa at fifth internode and loading rate: 4 m/s and 2.50 MPa at fifteenth internode and loading rate: 1 m/s, respectively.